The Effect of Tax Avoidance on Cost of Debt in Mining Companies Listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 Period - Febrianti, Anggi; Yuniawati, Ayi Srie; Ratnasari, Shofia Annisa (LPPM Universitas Sebelas April, 2025)
Tax avoidance is an activity that minimizes tax funds incurred by a company. This activity is legally effective, but goes against the government's efforts to increase state tax revenues. One of the tax avoidance practices that businesses can do is to implement external funds through debt costs. Debt costs are the rate of return arising from the company's debt transactions to external parties. This study attempts to determine the relationship between tax avoidance and debt costs in mining companies in 2021-2024. The data from this study use secondary data obtained from the Indonesia Stock Exchange for the period 2021–2024. The total sample used in this study was 84 samples. Sampling using purposive sampling technique. Data analysis using simple linear regression analysis using the SPSS 25 program. The results of the study indicate that the Tax avoidance variable has no effect on debt costs.